2020
DOI: 10.1016/j.envres.2020.110231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lockdown on the microbiological status of the hospital water network during COVID-19 pandemic

Abstract: The COVID-19 pandemic started in China in early December 2019, and quickly spread around the world. The epidemic gradually started in Italy at the end of February 2020, and by May 31, 2020, 232,664 cases and 33,340 deaths were confirmed. As a result of this pandemic, the Italian Ministerial Decree issued on March 11, 2020, enforced lockdown; therefore, many social, recreational, and cultural centers remained closed for months. In Apulia (southern Italy), all non-urgent hospital activities were suspended, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…These are all critical aspects related to Legionella persistence in man-made systems that contribute to a higher or lower legionellosis risk. The studies considered in Table 1 cover different water settings, including cooling towers [55][56][57], premise plumbing from hospitals [51,52,54,[58][59][60][61][62][63][64] and hotels [45,48,[64][65][66][67][68][69], residential potable water systems [46,70,71], and other facilities [72][73][74][75][76][77][78].…”
Section: Main Research Topicsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are all critical aspects related to Legionella persistence in man-made systems that contribute to a higher or lower legionellosis risk. The studies considered in Table 1 cover different water settings, including cooling towers [55][56][57], premise plumbing from hospitals [51,52,54,[58][59][60][61][62][63][64] and hotels [45,48,[64][65][66][67][68][69], residential potable water systems [46,70,71], and other facilities [72][73][74][75][76][77][78].…”
Section: Main Research Topicsmentioning
confidence: 99%
“…Chemical Disinfection Programs shape bacterial communities and reduce Legionella positivities (chlorination, chloramine, chlorine dioxide, copper-silver ionization, hydrogen peroxide and silver salts, NEOW) [51,52,54,56,61,62,66,72,73,[79][80][81] Effective temperature control reduces Legionella incidence [60,70,82] Water stagnation vs. water flushing [48,59,65,71,78,83]…”
Section: Microbial Control Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, particular attention has been paid to nosocomial legionellosis [ 8 , 10 , 11 , 12 , 13 , 14 ]. The association between drinking water and nosocomial legionellosis was first described about 40 years ago [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, 1.4 cases of LD per 100,000 populations were reported by the European Centre for Disease Prevention and Control in 2016. Recently, a study in Italy reported an incidence rate of 48.9 cases per 100,000 populations for legionellosis in 2018, of which 3.4% was of nosocomially acquired cases [42] . In Hong Kong, the incidence of LD was increasing from 0.16 cases/100,000 population in 2005 to 0.91 cases/100,000 population in 2015 [43] .…”
Section: Epidemiology Of Legionnaires' Diseasementioning
confidence: 99%